Personal Story and Public Identity as Axis of Value Response: Lessons on Literacy and Morality from John Henry Newman (1801-1890) and Ma Xiangbo (1840-1939) - Law, Cyril (2025)
In the hype of multi-/inter-disciplinarity, is the voi-ce or voices of theistic religions and the attendant philosophical moral awareness (etymologically bet-ter rendered as conscientização in Portuguese) still meant to be heard? Can classical tales of saints and sinners remain part of the canon of public literacy? How existential is the threat of “organised religions” or otherwise established ecclesiastical structures posed to society when they are accused of attempting to fight proxy crusades against humanitarian enlightenment under the guise of religious literature? Are tenets pro-pounded by scholars like Gavin D’Costa in Theology and the Public Square (2005) to be politely bracketed when discussing perennial values? Values that respon-sible media strive to propagate, particularly the value of human dignity eulogised by the life exemplars of great figures in times of existential crises of whatever magnitude. With these questions in mind, this article will hearken back to the stories of two “grandees” in the Roman Catholic tradition who left their marks on the pages of the development of modern English and Chinese literacy. Newman’s Apologia pro vita sua(1865) is just but one of the tactical devises for his defense of creedal integrity, while Ma Xiangbo engaged in catholicising the Chinese national ethos through educational literacy for close to half a century. We shall phenomenologically draw inspirations from their parallel vision and experience on what lends power to the medium of words and deeds in shaping informed public conscience in regard to the core values of truth, good, and beauty.

The Vital Signs of Roman Catholic Liturgical Music among the Cantonese-Portuguese-English Speaking Communities in Macau 羅馬天主教禮儀聖樂在澳門粵葡英三語群體間之生命力’ - Law, Cyril Jerome (2019)

Actio Ecclesiae: The Participation of the Lay Christian Faithful in the Liturgy of the Hours (c. 1174 Sec. 2) - Law, Cyril Jerome (The Jurist: Studies in Church Law and Ministry, 2023)

Joseph Ma Xiangbo – the John Henry Newman of China? An Attempt to Rehabilitate an Underdog “Father” of Chinese Catholicism 若瑟馬相伯 – 中國的若望享利紐曼? 試替一位無名的中華公教教父振聲 - Law, Cyril Jerome (Macau Ricci Institute Forum, 2019)

Minimising Maximum Illud: Early Resistance to Missionary Inculturation in China - Law, Cyril Jerome (Orientis Aura: Macau Perspectives in Religious Studies, 2022)

「紐曼樞機：兩心對話，一生皈依」澳門紐曼樞機藝文館開幕活動系列專題講座 （Special Lecture on Cardinal Newman for the Opening of the Centro de Cultura e Artes Performartivas Cardeal Newman de Macau） - Law, Cyril Jerome (2020)

Book Review: ‘The Catholic Invasion of China: Remaking Chinese Christianity’, by D. E. Mungello (Lanham, MD: Rowman & Littlefield, 2015) - Law, Cyril Jerome (Heythrop Journal, 2018)

澳門天主教教理培育委員會《天主教教理》卷二「基督奧跡的慶典」課程 - Law, Cyril Jerome (2019)

Translating Two Minds in the Tradition of One Faith: Considerations of Intercultural Dynamics in the parallels of John Henry Newman (1801-1890) and Joseph Ma Xiangbo (1840-1939) - Law, Cyril Jerome (Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular, 2021)
Interculturality is considered a constant given in the development of most major religious movements during the process of propagation coming into contact with diverse tongues, mores, and sentiments. And one of the chief, if not decisive, instruments contributing to this ever dynamic spread and reception of beliefs and cultures is translation. Christianity purports to be an incarnational religion, where the Word made flesh expresses the di-vine in human terms. Its doctrines are enshrined in a faith tradition that is developed largely through interpretation and translation. This short paper will cut into this sacral literary tradition by paralleling two influential mod-ern Christian thinkers, John Henry Newman from the Anglophone school, and Joseph Ma Xiangbo from the Orient, to see how attempts at translating the ideas and works of people from distinct cultural milieux is both reflec-tive of the necessary developmental nature of Christian teachings in the historical continuum of time and space, and indicative of the intellectual challenges that never cease to accompany the literary effervescence stem-ming from comparative religious studies.

Newman and the Ministerial Priesthood - Law, Cyril Jerome (Friends of the Ordinariate, 2018)

「道」與「導」：與聖紐曼樞機反思生命中皈依與教學之使命 Leading the Way - Reflecting on the Mission of Learning and Conversion of Life with St John Henry Newman (1801-1890) - Law, Cyril Jerome (2021)

馬相伯研究的點線面 – 生命、史料、信仰(On Ma Xiangbo Studies) - Law, Cyril Jerome (2019)